2022
DOI: 10.1007/s10163-022-01515-5
|View full text |Cite
|
Sign up to set email alerts
|

Generic foresight model in changing hygiene habits with the pandemic: use of wet wipes in next generations

Abstract: The vast use of wet wipes has now become a habitude, particularly following the altered perception of cleanliness during the pandemic and the encouragement towards using WW (wet wipe) to ensure parent’s and children’s hygiene. This study primarily aims to create a projection of the WW waste that will emerge in Turkey as a result of the promoted consumption by children who are predicted to retain the WW usage practices of their parents. In line with this habit adopted by children, the number of daily WW usage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The second is indirect introduction into combined sewer systems, where the sewer system carries both stormwater and wastewater (Di Nunno et al, 2021). In addition, WWTPs serving smaller towns and suburban areas are more likely to contain certain types of MaPs such as cotton buds, as well as other wastes such as condoms, wet wipes, sanitary pads and baby wipes (Alda-Vidal et al, 2020;Besley and Cassidy, 2022;Köklü et al, 2023). This suggests that people in urban areas are more environmentally aware and active than people in suburban areas.…”
Section: Wwtps As a Potential Source Of Plastic Pollution In The Envi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The second is indirect introduction into combined sewer systems, where the sewer system carries both stormwater and wastewater (Di Nunno et al, 2021). In addition, WWTPs serving smaller towns and suburban areas are more likely to contain certain types of MaPs such as cotton buds, as well as other wastes such as condoms, wet wipes, sanitary pads and baby wipes (Alda-Vidal et al, 2020;Besley and Cassidy, 2022;Köklü et al, 2023). This suggests that people in urban areas are more environmentally aware and active than people in suburban areas.…”
Section: Wwtps As a Potential Source Of Plastic Pollution In The Envi...mentioning
confidence: 99%
“…Recent scientific articles have shown that the movement of plastics over land and rivers is influenced by human activities, flood and storm events, hydrodynamics and their combinations. Interestingly, the majority of plastics do not reach the open sea but end up on beaches, float in coastal waters or accumulate on land and in river systems (Köklü et al, 2023;Sönmez et al, 2023). To address this problem, several innovative technologies have been developed and deployed to reduce pollution from MaPs.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…In addition, wet wipes consist of several fabrics, including natural and synthetic fibers. 14 Because Korea does not suggest pretreatment methods for the microbial test of wet towels and wet wipes in detail, the pretreatment methods to increase the recovery rates of microorganisms contaminated with samples of various fabrics should be prepared. Therefore, the objective of this study was to evaluate pretreatment methods and evaluate microbial contaminations in wet towels and wet wipes with the selected pretreatment method.…”
Section: Introductionmentioning
confidence: 99%